O cuidado segundo a vocação evangélica de São Francisco de Assis : contribuições dos estudos franciscanos à reflexão sobre o cuidado e suas implicações éticas - Hinrichsen, Luís Evandro (2016)
Care, according to Martin Heidegger, is the way of being of Dasein, answer to finitude. The being-there-in-theworld needs to foresee and respond to its needs [Besorgen], it needs to receive the other [Fürsorge], it is summoned to fate its existence towards the habitability of the world. Care is not an addition, but an essential note of human existence. This work, stemming from Heidegger’s existential analytics, investigates Saint Francis of Assisi’s gestures of care in Franciscan 1st century texts considering, among others, the 1223 Regula Bullata, the Wolf of Gubbio, the Testament, the Brother Sun Song and Perfect Joy. Saint Francis of Assisi, effectively, witnessed care by receiving, with privilege, the frail ones and noticing the presence of the Trinity in creation. The reflection on Care, valuing the study of Franciscan texts, requires explaining of the ethical principles that guide their exercise, for Care is intentionality, proximity, and encounter. The understanding of Care, presupposed to the edification of an inhabitable world through friendliness supposes overcoming the Cartesian-Newtonian analytical matrix view towards a systemic and integrative way of thinking and acting. In this way, from a context of fragmentation of vital experiences, the reflection on Care and its ethical principles allows the indication of pastoral signals. Signals that may contribute to the reflection on the challenges proposed to the Church in its different placements and areas of work.